Atlantis - Karst, Ken (Mankato, MN : Creative Education, 2015)
"An investigative approach to the curious phenomena and mysterious circumstances surrounding Atlantis, from historical accounts to popular mythic qualities to hard facts"--
Includes bibliographical references and index.
Keywords: Atlantis (Legendary place)